Node Energy Based Approach to Improve Network Lifetime and Throughput in Wireless Sensor Networks - Kumar, Hradesh; Singh, Pradeep Kumar (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Energy consumption is the one of the most important issue in wireless sensor networks. To improve the network lifetime energy consumption in the network must be less. In this paper, a cluster based approach is proposed to increase the network lifetime and throughput of the heterogeneous wireless sensor networks. The proposed approach combined the direct data transmission to base station with the cluster head transmission of data in wireless sensor networks. The proposed scheme uses the twice energy for advanced nodes in comparison to normal nodes. In the proposed approach, it is observed that results are found good with the use of 10 % of advanced nodes along with normal nodes in the network. However, on further increasing the advanced node deployment beyond deployment 30%, network lifetime and throughput of network start degrading. So, the proposed solution with 10% advanced node may be considered as the best suitable and acceptable solution for better network throughput and life time in WSNs.